2006
DOI: 10.1007/s11104-006-0019-y
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Fixation of Faba Bean (Vicia faba L.) Interacting with a Non-legume in Two Contrasting Intercropping Systems

Abstract: A field experiment was carried out to quantify biological nitrogen fixation (BNF) using the 15 N isotope natural abundance method in maize (Zea mays L.)/faba bean (Vicia faba L.) and wheat (Triticum aestivum L.)/faba bean intercropping systems. Faba bean was yielding more in the maize/faba bean intercropping, but not in the wheat/faba bean intercropping. Biomass, grain yield and N acquisition of faba bean were significantly increased when intercropped with maize, and decreased significantly with wheat, irrespe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
91
2
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 191 publications
(108 citation statements)
references
References 43 publications
11
91
2
4
Order By: Relevance
“…We found that, when root interactions were possible (no root partition), faba bean biomass and grain overyielded by 35% and 61%, respectively, with no N fertilization (P < 0.0001) and when fertilized with 150 kg ha −1 N, overyielding percentages were 28% and 35%, respectively (P < 0.0001) (Table S1). These results are similar to those reported previously (7). Also,…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…We found that, when root interactions were possible (no root partition), faba bean biomass and grain overyielded by 35% and 61%, respectively, with no N fertilization (P < 0.0001) and when fertilized with 150 kg ha −1 N, overyielding percentages were 28% and 35%, respectively (P < 0.0001) (Table S1). These results are similar to those reported previously (7). Also,…”
Section: Resultssupporting
confidence: 93%
“…Facilitation occurs when one species increases the growth of other species through a wide range of processes (10). Facilitative effects may be direct (e.g., by shade or protection from harsh conditions) or indirect (e.g., when one species reduces attack by pathogens or herbivores on other species) (11-13).Legume/cereal intercropping systems have been widely studied in the context of diversity and ecosystem function and commonly overyield, because dinitrogen (N 2 ) fixation by legumes increases ecosystem nitrogen (N) supply (7,8), an example of facilitation. This facilitation is important to agriculture on a large scale, because application of chemical N fertilizer decreases biological N 2 fixation by legumes.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…It was previously observed that %Ndfa of the legume increased due to an N-sparing effect (N concentration in legume rhizosphere is reduced) by the non-legume (Danso et al 1987). A similar observation was also reported by a recent study (Fan et al 2006). Greater Ndfa% by intercropped legume could be further explained by the probable reduction of nitrate concentration in the rhizosphere due to higher nonlegume uptake of nitrate, which may reduce its toxic effect on Rhizobium (Kurdali et al 2003).…”
Section: Discussionsupporting
confidence: 85%